2019
DOI: 10.1177/0886260519860078
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Female Homicide Perpetrators

Abstract: Neurobiology of female homicide perpetrators is not well understood. Data from private interviews and examinations of females were re-analyzed comparing those who committed homicide ( n = 9); other violent crimes, no known homicide ( n = 51); nonviolent crimes, no known violent convictions ( n = 49); and noncriminals ( n = 12). Homicide perpetrators suffered the most childhood sexual abuse (CSA); most recent abuse; had the most neurological histories, mainly traumatic brain injuries (TBIs); most health care ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…complications and neurocognitive deficits have been linked to youth violence, 19 so has traumatic stress due to experiences such as neglect, abuse, family conflict, poverty and bullying. 18,[20][21][22][23] Chronic stress related to these types of experiences have been associated with changes in the development and functioning of the hypothalamic-pituitary-adrenocortical axis in ways that compromise adaptive responses to stress. 23 Also consistent with previous studies, we found that homicidal ideation and homicide/assault victimizations were most common among patients in the lowest zipcode income quartile, regardless of race or ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…complications and neurocognitive deficits have been linked to youth violence, 19 so has traumatic stress due to experiences such as neglect, abuse, family conflict, poverty and bullying. 18,[20][21][22][23] Chronic stress related to these types of experiences have been associated with changes in the development and functioning of the hypothalamic-pituitary-adrenocortical axis in ways that compromise adaptive responses to stress. 23 Also consistent with previous studies, we found that homicidal ideation and homicide/assault victimizations were most common among patients in the lowest zipcode income quartile, regardless of race or ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…These data elements were not available in the HCUP NIS but are likely to influence the occurrence of homicidal ideation or victimization by homicide or assault. 18,20,22,27,28 In addition, in this study we examined the occurrence of homicide and assault together because of the way ICD-9 and ICD-10 codes are designed. However, racial disparity of aggravated assault and other socio-demographic characteristics may not resemble that of murder.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary Cortisol was evaluated similar to previous studies for comparison, 9,10,17 immediately upon awakening (AM) before they ate, drank, smoked or exercised, and again before dinner (PM). Participants were asked not to eat, drink anything other than water, smoke or exercise between their noon meal and the PM saliva collection.…”
Section: Methodsmentioning
confidence: 99%
“…The stress hormone cortisol can be dysregulated later in life among victims of abuse. 17 Cortisol is a primary product of the hypothalamic-pituitary-adrenal (HPA) axis, a key component of the stress response. Normally, a resting basal cortisol diurnal pattern shows a peak in the morning and then a gradual decrease throughout the day, creating a steep diurnal cortisol slope between morning (AM) and evening (PM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation